1996
DOI: 10.1007/bf00019462
|View full text |Cite
|
Sign up to set email alerts
|

Defence-related gene activation during an incompatible interaction between Stagonospora (Septoria) nodorum and barley (Hordeum vulgare L.) coleoptile cells

Abstract: Two previously unidentified cDNA clones (bsi1 and bpr1-1) were isolated by differential hybridization from a cDNA library of Stagonospora (Septoria) nodorum (Berk) Castellani & E.G. Germano (teleomorph Phaeosphaeria (Leptosphaeria) nodorum (E. Muller) Hedjaroude-challenged barley (Hordeum vulgare L.) coleoptiles. bsi1 encoded a cysteine-rich protein containing 89 amino acids (aa) with a relative molecular mass (M(r)) of 9405. Protein sequence homologies showed that Bsi1 was very similar to an aluminium-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 50 publications
(68 reference statements)
0
22
0
Order By: Relevance
“…The farnesylated protein encoded by SSBI-B9 has been found in Hordeum vulgare to be a nuclear protein involved in stress response and leaf senescence (Barth et al 2004). SSBI-D4, SSBI-D9, SSBII-A3, and SSBI-A4 encoded a Wber protein Fb19 (Chow et al, unpublished), a dehydration-responsive family protein (Albertini et al 2004), a type-1 pathogenesis-related protein (Stevens et al 1996), and a DNAJ heat shock N-terminal domain-containing protein (Chow et al, unpublished), respectively, which have been widely studied in association with stress response. SSBI-E2 encoded a 34 kD Wbrillin-like protein, the major constituent of elastin-associated extracellular microWbrils, and has been recently identiWed in a network of rice genes associated with stress response (Cooper et al 2003).…”
Section: Predicted Function Of Up-regulated Defsmentioning
confidence: 97%
“…The farnesylated protein encoded by SSBI-B9 has been found in Hordeum vulgare to be a nuclear protein involved in stress response and leaf senescence (Barth et al 2004). SSBI-D4, SSBI-D9, SSBII-A3, and SSBI-A4 encoded a Wber protein Fb19 (Chow et al, unpublished), a dehydration-responsive family protein (Albertini et al 2004), a type-1 pathogenesis-related protein (Stevens et al 1996), and a DNAJ heat shock N-terminal domain-containing protein (Chow et al, unpublished), respectively, which have been widely studied in association with stress response. SSBI-E2 encoded a 34 kD Wbrillin-like protein, the major constituent of elastin-associated extracellular microWbrils, and has been recently identiWed in a network of rice genes associated with stress response (Cooper et al 2003).…”
Section: Predicted Function Of Up-regulated Defsmentioning
confidence: 97%
“…In most species in which careful genetic characterization has been made, thionins appear to be expressed as non-toxic propeptides activated upon pathogenic attack [32][33][34]. Analysis of thionin cDNA showed that thionins have a common gene structure with an approximately 20-amino acid-long leader peptide and an approximately 60-amino acid-long trailing acidic peptide, which neutralizes the basic toxin [15].…”
Section: Historymentioning
confidence: 98%
“…The original laboratory isolate of S. nodorum, coded SG, which was pathogenic on wheat but not barley, was obtained from Institute of Arable Crop Research (IACR), Long Ashton, UK and was the same as that used by Stevens et al (1996). Other isolates of S. nodorum used in this study were freshly isolated from field material using the following techniques : infected wheat leaves with Staganospora-like lesions were placed on damp filter paper in a sealed polythene box and incubated at 18mC for 3-5 d under continuous near UV light (Sylvania F15TB\BL8 15W).…”
Section: Isolation Culture and Preservation Of Fungimentioning
confidence: 99%